2017
DOI: 10.4103/neuroindia.ni_101_16
|View full text |Cite
|
Sign up to set email alerts
|

Potential for differentiation of glioma recurrence from radionecrosis using integrated 18F-fluoroethyl-L-tyrosine (FET) positron emission tomography/magnetic resonance imaging: A prospective evaluation

Abstract: Synergetic effect of multiple MR parameters evaluated together in addition to FET PET uptake highlights the fact that integrated 18F-FET PET/MRI might have the potential to impact management of patients with glioma by timely and conclusive recognition of true recurrence from radiation necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 1 publication
1
25
0
Order By: Relevance
“…In their retrospective study on 32 treated glioma patients undergoing simultaneous 18 F-FET PET/MRI and MRI spectroscopy to identify suspect GR, Sogani et al. found that the addition of 18 F-FET parameters slightly improved sensitivity of advanced MRI and magnetic resonance spectroscopy (MRS), with sensitivity, specificity, and diagnostic accuracy of 100, 85.7, and 96.87% for 18 F-FET PET/MRI and 96, 85.7, and 93.75% for advanced MRI and MRS ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their retrospective study on 32 treated glioma patients undergoing simultaneous 18 F-FET PET/MRI and MRI spectroscopy to identify suspect GR, Sogani et al. found that the addition of 18 F-FET parameters slightly improved sensitivity of advanced MRI and magnetic resonance spectroscopy (MRS), with sensitivity, specificity, and diagnostic accuracy of 100, 85.7, and 96.87% for 18 F-FET PET/MRI and 96, 85.7, and 93.75% for advanced MRI and MRS ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several studies have reported better diagnostic accuracy by simultaneous use of PET and PWI (On-line Table 4). 36,38,51,54,55,[67][68][69][70][71][72][73][74][75] In a pilot study of 30 HGGs, ASL provided better results than DSC and FDG in detecting TR. However, DSC provided better spatial resolution with improved sensitivity when predominant TR with superimposed regions of predominant mixed RN were excluded while ASL sensitivity remained unchanged.…”
Section: Combined Use Of Pet and Perfusion Mr Imagingmentioning
confidence: 95%
“…70 Integrated PET/MR imaging simultaneously acquires functional and structural parameters, which might have the potential to impact patient management by timely and accurate recognition of TR. 55,71,72 AATs show superior contrast to that of FDG because of low uptake in the normal brain tissue. [ 18 F] FET provides valuable information for re-radiation treatment planning of HGGs by differentiating metabolically active tumor from normal brain tissue.…”
Section: Combined Use Of Pet and Perfusion Mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary brain tumors are noted to overexpress amino acid transporters and increase amino acid uptake compared to normal brain. 3 The most promising amino acid imaging tracers include 18 Fluoro-O-(2) fluoroethyl-l-tyrosine ([ 18 F]FET), 4 - 6 [ 11 C] Methionine (MET), and 18 F-dihydroxyphenylalanine ( 18 F-DOPA) are similarly sensitive and specific for tumor regrowth. 7 Studies primarily in gliomas have reported [ 11 C]MET has 70-100% sensitivity and 60-100% specificity for TR.…”
Section: Introductionmentioning
confidence: 99%